3 New generation hydrogel endovascular aneurysm treatment (HEAT) trial. (July 2018) - Abi-Aad, K; Ward, J; Kniss, J; Aoun, R; Krishna, C; Welz, M; Tian, F; Bendok, B
Abstract : Introduction: Recurrence remains a limitation of endovascular aneurysm treatment. The Hydrogel Coil (Microvention, Aliso Viejo, CA) that constitutes a platinum core surrounded by a hydrogel coat was developed to enhance packing density and healing within an aneurysm, with the ultimate goal of improving durability rates. The first-generation HydroCoil showed positive results in terms of aneurysm recurrence; however, widespread adoption was limited by technical challenges. For this purpose, a second-generation Hydrogel Coil (HES – HydroCoil Embolic System) was developed. Its design allows for longer working times (20–30 min), and an ease of use which seems to parallel platinum coils. The New Generation Hydrogel Endovascular Aneurysm Treatment (HEAT) Trial aimed to compare the second generation HydroCoil Embolic System with bare platinum coils in a study of 600 subjects. Methods: This is a randomized, controlled, multicenter, post-market clinical trial. Subjects between 18 and 75 years of age with ruptured or unruptured intracranial aneurysms (3–14 mm in size) who were amenable to endovascular treatment were randomized in a 1:1 fashion to each of the treatment arms in 46 participating sites. The protocol stipulated that subjects randomized to the HES arm be treated with at least 90% second-generation hydrogel coils and subjects randomized to the bare platinum arm strictly receive bare platinum coil. The primary endpoint of the trial was aneurysm recurrence over an 18 month follow-up period. Secondary endpoints included packing density, initial occlusion, retreatment, hemorrhage from the treated aneurysm, mortality, and aneurysm occlusion stability. Results: Enrollment began on June 20, 2012 and ended in January 15, 2016. Among screened subjects (n=3971), 600 patients were randomized (HES n=297 and bare platinum n=303). Aneurysm size was similar in both arms with a mean of 6.86 mm in the HES group and 6.93 mm in the bare platinum group. Recanalization rates were 4.4% for the HES arm and 15.4% for the bare platinum arm (p<0.001). In terms of clinical outcomes, there were no differences in adverse events (HES: 44%, bare platinum: 47%, p=0.498), mortality (HES: 2%, bare platinum: 3%, p=0.641), retreatment (HES: 5% and bare platinum: 8%, p=0.162), and re-hemorrhage rates (HES: 2%, bare platinum: 3%, p=0.297) between both arms. Conclusion: In the HEAT trial, the second-generation Hydrogel Coil is found to be superior to the bare platinum coil in reducing aneurysm recurrence rates. In addition, long-term clinical assessment was similar between both arms. Our study results support the preferential use of Hydrogel coils for the endovascular treatment of intracranial aneurysms. Disclosures: K. Abi-Aad: 1; C; MicroVention, Inc. J. Ward: 1; C; MicroVention, Inc. J. Kniss: 1; C; MicroVention, Inc. R. Aoun: None. C. Krishna: None. M. Welz: None. F. Tian: None. B. Bendok: 1; C; MicroVention, Inc.